2021
DOI: 10.1080/24759651.2021.1926621
|View full text |Cite
|
Sign up to set email alerts
|

Screening, optimization and characterization of poly hydroxy butyrate from fresh water microalgal isolates

Abstract: Microalgae, especially Chlorella sp., have been used for centuries as food and currently their biotechnological potential is notable for the presence of several compounds relevant to the market, like PHB. Microalgae are appealing because of the increasing demand for biopolymers like PHB. Therefore, the present study is aimed to determine the efficacy of biomass production and yield of PHB producing microalgae isolated and identified by phylogenetic analysis. The parameter was optimized as pH 7, temperature 30°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…The peaks from 1132 cm −1 to 826 cm −1 were associated with the stretching vibrations of C-O and C-C, while that at 1183 cm −1 was associated with the asymmetric stretching vibration of the C-O-C group. The peaks at 1300 and 1100 cm −1 correspond to the symmetric stretching of the C-O-C group, according to Heitmann et al (2016) [52], who reported the characterization of a nanostructured niobium oxyhydroxide dispersed PHB film, and Selvaraj et al ( 2021) [53].…”
Section: Ft-ir Spectrummentioning
confidence: 92%
“…The peaks from 1132 cm −1 to 826 cm −1 were associated with the stretching vibrations of C-O and C-C, while that at 1183 cm −1 was associated with the asymmetric stretching vibration of the C-O-C group. The peaks at 1300 and 1100 cm −1 correspond to the symmetric stretching of the C-O-C group, according to Heitmann et al (2016) [52], who reported the characterization of a nanostructured niobium oxyhydroxide dispersed PHB film, and Selvaraj et al ( 2021) [53].…”
Section: Ft-ir Spectrummentioning
confidence: 92%
“…In addition, Microcystis aeruginosa has been shown to exhibit PHB concentrations of up to 0.49 ± 0.5 mg/L [79]. Selvaraj et al [80] recorded maximum 80% PHB production by Chlorella sp. The highest recorded PHB content of 27% dry weight was achieved by Mehariya et al [81] during cultivation of Chlorococcum sp.…”
Section: Polyhydroxyalkanoatesmentioning
confidence: 99%
“…Another study was done on chlorella species for PHB content. Results indicated it has 2.15 g/500 mL PHB content [ 39 ]; thus, there rises a need for gene-editing tools like CRISPR for modifying enzyme-producing PHB/PHA content in microalgae species for up-scaling bioplastic production.…”
Section: Modern Bioengineering Techniques To Enhance Production Of Bi...mentioning
confidence: 99%
“…According to previous reports, the maximum concentration (80%) of PHB is produced by Chlorella vulgaris [ 39 ]. A number of cyanobacteria species ( Arthrospira, Nostoc muscorum , Synechocystis PCC6803 and Synechococcus sp.…”
Section: Introductionmentioning
confidence: 99%